The great illusion. The praxis of the intellectual multitudinous in the Cognitive Capitalism paradigm - Maniglio, Francesco (2016)
We employed Cognitive Capitalism approach to shed light on the knowledge in the circuit shortage, on the fact that the subsumption of society by market logic exceeds the objective and subjective development of a knowledge-based economy. The concept of multitude indicates a socialization of the productive forces and potentially subversive, revolutionary and communist community at a global level. The aim of this article is to denounce this position from the practice of multitudinous intellectual in struggle for the common. We adopt the hypothesis that Luciano Gallino expressed in terms of cognitive capture, properly referring to the lack of opposition to the attacks of the class enemy and substantial acceptance of its theoretical paradigms.